Urgent double-balloon enteroscopy for reduction of jejuno-jejunal intussusception and polypectomy in Peutz-Jeghers syndrome - Yoshiko Nakayama; Sawako Kato; Shingo Kurasawa; Reina Nakamura; Tomoaki Suga; Masahiro Kurozumi (Elsevier, 2020)
A 13-year-old girl presented with sudden-onset colicky abdominal pain and biliary vomiting. She was diagnosed with Peutz-Jeghers syndrome 2 months previously based on mucocutaneous pigmentation and hamartomatous polyposis. On diagnosis of Peutz-Jeghers syndrome, in addition to colonoscopy and esophagogastroduodenoscopy, antegrade and retrograde double-balloon enteroscopies were performed, and >10 hamartomas were resected. She was scheduled for additional elective double-balloon enteroscopy for total small-bowel observation. On visiting the emergency unit, enhanced abdominal computed tomography showed jejuno-jejunal intussusception with a polyp. There were no ischemic signs in the invaginated bowel. Urgent antegrade double-balloon enteroscopy performed 5 hours after onset of acute abdominal symptoms revealed a large polyp with intussusception stalk in the jejunum, and simultaneous reduction of intussusception and endoscopic mucosal resection of the polyp were performed successfully. There were no endoscopy-related complications, and emergent laparotomy was avoided. The patient has been asymptomatic, and total gastrointestinal screening is scheduled every 2 years. This is the first case in which emergent laparotomy was avoided by urgent double-balloon enteroscopy in an adolescent with symptomatic jejuno-jejunal intussusception. Non-surgical management of small-bowel polyps in pediatric patients with Peutz-Jeghers syndrome is beneficial as laparotomy can cause bowel adhesion and increases risk of incomplete balloon-assisted enteroscopy.